How to Control the Fiscal Costs of Public-Private Partnerships - Irwin, Timothy (IMF How To Notes; How-To Note ;, 2018)
This note discusses what finance ministries can do to ensure that public-private partnerships (PPPs) are used wisely. By inviting private participation in infrastructure development and service provision, PPPs can help improve public services. Yet, strong governance institutions are needed to manage risks and avoid unexpected costs from PPPs. While in the short term, PPPs may appear cheaper than traditional public investment, over time they can turn out to be more expensive and undermine fiscal sustainability, particularly when governments ignore or are unaware of their deferred costs and associated fiscal risks. To use PPPs wisely governments should (1) develop and implement clear rules for their use; (2) identify, quantify, and disclose PPP risks and expected costs; and (3) reform budget and government accounting frameworks to capture all fiscal costs comprehensively.